Rekonstruksi Ekonomi Makro Islam Melalui Pendekatan Konseptual Kebijakan Fiskal dan Tantangan Kelangkaan Sumber Daya - Putri Amirah Hajarani; Imsar Imsar (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
This study aims to reconstruct the Islamic macroeconomic paradigm by focusing on fiscal policy and responses to resource scarcity. Using a descriptive qualitative approach based on literature review, the study reveals that fiscal policy in Islam functions not only as a tool for economic stabilization but also as an instrument for equitable distribution and sustainable resource management. Historical analysis of fiscal practices during the Prophet Muhammad's era illustrates a zakat-, kharaj-, and fai-based system managed transparently and justly through baitul mal. In the modern context, challenges such as inequality, resource exploitation, and energy crises require a new approach grounded in maqashid shariah as the foundation of macroeconomic planning. Therefore, reconstructing Islamic macroeconomics is essential to establishing a just, sustainable, and spiritually rooted economic system.